Institutional Development and Efficiency of Fishermen Cooperatives in Marine Fisheries: A Case Study from Kerala - Jeyanthi, P.; Chandrasekar, V.; Ashok, Arathy; Nair, V. Radhakrishnan; Thomas, K. Jesy; Jos, K. D.; Gopal, Nikita (Fishery Technology, 2018)
Fishermen co-operatives have played a significantrole in improving the livelihood of millions offishermen. The extended co-operative services andefficiency of co-operatives over the years make theco-operatives effective. This paper presents theinstitutional development and efficiency of twofishermen co-operative societies viz., Njarakkal(Society I) and Manassery (Society II) in Ernakulamdistrict, Kerala. It was revealed that there werespatial and temporal differences in institutionaldevelopment between two societies while deliveringco-operative services. From the results of DataEnvelopment Analysis (DEA), it was found that themean technical efficiencies estimated using VariableReturns to Scale (VRS) were 96 and 87% inSociety I in and Society II respectively. The scaleefficiency revealed that the Society II is operating atsub-optimal scale size than Society I. The amountof loan disbursed and repayment, income from fishmarketing services were the factors responsible forthe efficiency of co-operatives.